2018
DOI: 10.6008/cbpc2179-6858.2018.006.0008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do teor de Cumarina e atividade antifúngica de frações de Óleo de Cumaru

Abstract: Os cumaruzeiros são árvores neotropicais originárias de países da América Central e América do Sul. Os frutos destacam-se quanto às potencialidades comerciais e fitoterápicas, e suas sementes, há mais de um século, são comercializadas por extrativistas da Amazônia. Este estudo teve por objetivo analisar o teor de cumarina (1,2-benzopirona) e a atividade antifúngica de frações de óleo obtidas de sementes de cumaru produzidas no município de Alenquer, Pará, Brasil. As frações foram obtidas por extrações sucessiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…to 96%, obtaining the highest yield and the isolation of 3.4% of coumarin in the hexanic fraction. However, in the dichloromethane and ethanolic fractions, in addition to simple coumarin, hydrocoumarin (3,4-dihydro-2H-1-benzopyran-2-one or 3,4-dihydrocoumarin) was identified [82]. This substance, belonging to the class of coumarins, has also been reported in the extract of D. punctata seeds [10] and this study found it in the extracts of branches, residues, and seeds.…”
Section: Discussionmentioning
confidence: 50%
“…to 96%, obtaining the highest yield and the isolation of 3.4% of coumarin in the hexanic fraction. However, in the dichloromethane and ethanolic fractions, in addition to simple coumarin, hydrocoumarin (3,4-dihydro-2H-1-benzopyran-2-one or 3,4-dihydrocoumarin) was identified [82]. This substance, belonging to the class of coumarins, has also been reported in the extract of D. punctata seeds [10] and this study found it in the extracts of branches, residues, and seeds.…”
Section: Discussionmentioning
confidence: 50%
“…Willd., popularly known as cumaru, is a large tree with a wide distribution across the Amazon [26]. The wood has a very high density and the seeds are rich in coumarin [27], which is widely used in the production of pharmaceutical products, cosmetics, herbicides, fungicides, and drinks, among other applications, which justifies the high demand for this species in national and international markets [28].…”
Section: Introductionmentioning
confidence: 99%